2010
DOI: 10.2478/v10085-009-0045-0
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary malacological investigation on the loess profile at Zmajevac, Croatia

Abstract: More than 5 500 specimens of 37 terrestrial snail species were collected from a loess paleosol section at Zmajevac village, Croatia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 5 publications
1
26
0
2
Order By: Relevance
“…Analysis of the mollusc species from Fruska Gora was started by Endre Krolopp and Pál Sümegi in 2000 [1][2][3][5][6][7][8]111]. Unfortunately, we have only a few malacologically analyzed profiles from the eastern part of the mountain that cover 1200-1500 years long intervals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of the mollusc species from Fruska Gora was started by Endre Krolopp and Pál Sümegi in 2000 [1][2][3][5][6][7][8]111]. Unfortunately, we have only a few malacologically analyzed profiles from the eastern part of the mountain that cover 1200-1500 years long intervals.…”
Section: Discussionmentioning
confidence: 99%
“…But it can be observed that the dominance changes and the decrease of the proportions of thermophilous species occurred in a consistent way in several areas [1,3,26].…”
Section: The Last Glacial Environment History and Paleobiogeographicamentioning
confidence: 99%
See 2 more Smart Citations
“…A szelvényben kialakított három mintavételi horizont mindegyikéből egyedi malakofauna került elő, így szükségszerűen 3 malakológiai zónára lehetett felosztani a szelvényünket. edentulus együttes jelenléte arra enged következtetni, hogy ez a malakológiai horizont a középső-pleisztocénben fejlődött ki (Ložek, 1964;Krolopp, 1973;Molnár et al, 2010Molnár et al, , 2011. Ezt bizonyítja a szelvényen mért IRSL kormeghatározási adat is, mely a szelvény 25,64 méterén 217.000±22.000 cal BP évnek adódott (Galović et al, 2009), ami valószínű, hogy a MIS 7a interglaciálisnak felel meg (Lisieczki & Raymo, 2005;Tzedakis et al, 2006;Gibbard & Cohen, 2008 Molnár et al, 2010 A következő malakológiai horizont szükségszerűen 13 és 11,5 méter között található, a ZS2 paleotalaj és a ZL3 löszréteg átmeneténél.…”
Section: A Szelvény Malakológiai Vizsgálatának Eredményeiunclassified